INOVASI PEMBELAJARAN IPAS MELALUI PENGGUNAAN MEDIA DIORAMA MATERI EKOSISTEM RANTAI MAKANAN UNTUK MENINGKATKAN PEMBELAJARAN SISWA DI SEKOLAH DASAR - Vina Indah Saputri; Nuhyal Ulia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Research stems from students low comprehension of abstract ecosystem concepts and the limited variety of instructional media used by teachers. A descriptive qualitative approach was employed, involving fifth-grade students and teachers at SDN Banyumanik 01 Semarang as research subjects. Data collection techniques included observation, interviews, and documentation. The results revealed that the use of diorama media significantly enhanced students’ engagement and comprehension of the subject matter. This was evidenced by an increase in the average score of the Mid-Semester Assessment (PTS), from 70 to 85, after the implementation of diorama-based learning. Additionally, students demonstrated success in three main indicators based on observation and interview data: collaboration, responsibility, and communication skills. Throughout the learning process, students showed enthusiasm and active participation. Therefore, it can be concluded that diorama media is an effective tool to improve elementary school students learning outcomes, especially in food chain topics within IPAS learning.